Case report: The case report of ofatumumab, a fully human anti-CD20 monoclonal antibody, in the treatment of KLHL11 encephalitis - Deng, Min; Zeng, Fei; Kong, Zhaohong; Li, Tao (Frontiers in Immunology, 2024)
Anti-kelchlike protein 11 (KLHL11) encephalitis was first reported in 2019. This disease is very rare. The prevalence is higher in men than in women. Few female cases have been described. The most common clinical manifestations of this disease are syndromes affecting the brainstem and cerebellum. There are few reports on epilepsy and hallucinations as main clinical manifestations of KLHL11 encephalitis. We report a case of KLHL11 encephalitis in a female with epilepsy and hallucinations as the primary symptom. Her EEG showed a large number of epileptiform waves could be seen in the bilateral temporal and sphenoid areas during the waking and sleeping stages. Her head MRI was normal. No tumors were found using PET/CT scan and tumor marker measurements. Her symptoms recurred and worsened soon after treatment with immunoglobulin and methylprednisolone. Fortunately, epilepsy and hallucinations were effectively controlled after six times of subcutaneous injection of ofatumumab. Ofatumumab is a CD20 monoclonal antibody that induces B cell depletion. Current studies show that KLHL11 encephalitis is mediated by T cell immunity. However, in this case, satisfactory clinical effects were observed using CD20 monoclonal antibodies to treat KLHL11 encephalitis. This is the first report of induced B cell depletion in the treatment of KLHL11 encephalitis. This may provide a potential treatment option for KLHL11 encephalitis.